Bi-Fe Doping and Mechanochemical Treatment of Vanadium Phosphate Catalysts for Selective Oxidation of N-Butane to Maleic Anhydride - Goh, Chee Keong (2006)
The introduction of Bi-Fe as dopants and mechanochemical treatments were employed in the preparation of catalyst precursor, VOHPO₄•0.5H₂O which was synthesised by reduction of VOPO₄∙2H₂O using isobutanol and followed by calcination in a flow of n-butane/air mixture (0.75 % n-butane in air) for 75 h at 673 K. Several methods such as XRD, SEM, ICP-AES, surface area measurements, redox titration, H₂-TPR and O₂-TPD were used to characterise the catalysts. The catalytic properties for selective oxidation of n-butane have also been carried out. The experimental results indicated that the addition of Bi-Fe dopants into the lattice of vanadium phosphate catalysts had decreased the surface area of the catalysts, except the catalyst doped with higher concentration of Bi. Besides, the Bi-Fe doped catalysts had promoted the formation of αII-VOPO4 phase and consequently decreased the crystallite structure of (VO)2P2O7. It was found that the morphologies of the Bi-Fe doped catalysts were affected by the ratios of dopant/V. The Bi-Fe doped catalysts were found to give delecterious effect to the conversion of n-butane. However, maleic anhydride selectivity was increased due to excess existence of V5+ phase. A good correlation was found between n-butane conversion and the amount of oxygen species associated to V4+ phase. The mechanochemical treatment using high energy planatary ball milling performed on catalyst precursors, VOHPO4•0.5H2O had increased the FWHM and reduced the crystallite size of the catalysts and consequently increased their surface area. However, longer milling to 120 min led to a reduction in the surface area of the catalyst due to the reagglomeration of the materials. The morphologies of rosette-shape for the catalysts were lost after the process of ball milling. The 60 min ball milled catalyst showed an increase on the reactivity and mobility of the oxygen lattice by lowering the reduction temperature and induced higher amount of oxygen species removed. An increase of the oxygen species associated with V4+ phase which was correlated to the catalytic activity and a slightly higher amount of oxygen species linked to V5+ phase also contributed to the activity. In the case of different milling media, the catalyst ball milled in dry medium drastically decreased the surface area due to the agglomeration of fracture solids, where may be the main contribution to the poor catalytic performance of the catalyst. The adoption of the solvent such as cyclohexane and ethanol improved the surface area and morphologies of the catalysts. A 30 min-milled catalyst in ethanol showed the highest maleic anhydride selectivity than unmilled and milled in dry medium and cyclohexane under the same condition. However, cyclohexane was found the best solvent for n-butane conversion for 30 min milled material.